Evaluasi Instrumen Pengukuran Kinerja Karyawan menggunakan Analisis Validitas dan Reliabilitas pada Tour and Travel Haji dan Umroh - Puan Nabilla; Rizky Hariyanto; Fahmi Mardiah; Ernawati Ernawati; Yuliana Yuliana; Rahmiati Rahmiati (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
The Hajj and Umrah travel service industry relies heavily on employee performance to deliver professional and high-quality services. However, accurate performance evaluation requires measurement instruments that are empirically validated and reliable. The main problem addressed in this study is the lack of empirical evidence regarding the validity and reliability of employee performance and work motivation measurement instruments used in Hajj and Umrah travel companies. This study aims to examine the validity and reliability of the measurement instruments for employee performance and work motivation. A quantitative descriptive approach was employed. Data were collected using a five-point Likert scale questionnaire distributed to 32 employees. The instrument was developed based on Robbins’ (2006) performance indicators, Moeheriono’s (2012) contextual performance concept, and Self-Determination Theory proposed by Deci and Ryan (2017). Data analysis was conducted using Pearson Product Moment validity testing and Cronbach’s Alpha reliability testing with IBM SPSS. The results indicate that all 24 questionnaire items are valid, with correlation coefficients exceeding the r-table value (0.349) and statistically significant at ? = 0.05. The reliability test produced a Cronbach’s Alpha value of 0.940, indicating very high internal consistency. These findings confirm that the instrument is valid, reliable, and appropriate for measuring employee performance and work motivation in Hajj and Umrah travel service companies.